Осіння кампанія Армії УНР 1920 р. - Плазова, Т. І. (Видавництво Львівської політехніки, 2012)
Розглянуто причини припинення бойових дій регулярною Армією УНР восени 1920 року. Проаналізовано особливості військово-політичної стратегії керівництва УНР щодо продовження антибільшовицької боротьби після остаточної втрати території України восени 1920 р. At this article is elucidated the main reasons of the cessation fighting actions of the regular Army UPR at autumn 1920 year. Also there are analysed the peculiarities of military strategy of leaders UPR in order to continue antibolshevik fight after final loss the Ukrainian territory at the same time.